Outcome of three dimensional osteotomy for cubitus varus deformity - Das, Krishna Priya; Datta, Nakul Kumar; Khan, Mohammad Zahidulhak; Islam, Jahidul; Chowdhury, Rumpa Mani (International Journal of Research in Orthopaedics, 2021)
Background: Cubitus varus is the most common angular deformity resulting from supracondylar fracture of the humerus in children and adults. There are several options for correcting this deformity, but three dimensional osteotomy is now a popular method for the operative treatment of cubitus varus deformity. Objective of current study was to evaluate clinical and radiological outcome of three dimensional corrective osteotmy for cubitus varus deformity. Methods: This prospective interventional study was conducted in the department of orthopaedic surgery, BSMMU, Shahbag, Dhaka from January 2016 to September 2020. Within this period, total 40 cases of cubitus varus deformity, age ranging from 8-20 years that has the inclusion criteria was enrolled as a study sample with proper consent. All the data were analyzed statistically by using SPSS-22. Results: The results of present study showed significantly improved carrying angle, range of motion, internal rotation angle at the time of final follow-up period of six months or more. The outcome of the subjects was graded as excellent in 16 (40%), good in 18 (45%), fair in 4 (10%) and poor in 2 (5%) patients. Excellent, good and fair results were considered as satisfactory outcome and only poor result was considered as unsatisfactory outcome. Conclusions: After analyzing the results of present study it can be concluded that three dimensional osteotomy is a safe technique with satisfactory outcome in treatment of cubitus varus deformity.